(untitled) (INNOVATIVE ECONOMY, 2023)
Zhyvko M.A., Nipialidi O.Yu. CIVILIZATIONAL DETERMINANTS OF SOCIAL AND ECONOMIC POLARIZATION OF COUNTRIES Purpose. The purpose of the article is to analyse and study of the influence of civilizational factors on the social and economic polarization of countries in order to identify the main dependencies, reveal their new trends and develop recommendations to reduce their negative impact on national economies. Methodology of research. The following scientific methods were used in the research process to achieve the goal: analysis of historical data – to determine historical events and cultural processes that influenced the growth and decrease of polarization of various regions and countries; cultural analysis – to establish the cultural aspects of different countries (language, religion, traditions, identity), taking into account their impact on the social and economic structure and distribution of resources; economic analysis – to assess economic indicators in order to establish the relationship between economic factors, social and economic polarization; to assess economic indicators to establish the relationship between economic factors and social and economic polarization; geographical analysis – for the purpose of researching the geographical features of countries (geographic location, climatic conditions, availability of natural resources) to determine the factors influencing economic and social development; modelling and statistical analysis – to identify statistical relationships between various aspects of civilization and the level of polarization; benchmarking – to compare data between different countries and regions in order to identify common and distinctive features that may be associated with social and economic polarization. Findings. It is studied how certain aspects of culture, such as language, religion, traditions, affect the level of social and economic polarization in countries. The role of certain historical events in shaping the structure of society and the level of social and economic inequality has been established. It has been confirmed that the influence of economic factors on social and economic polarization, such as the level of income, unemployment. It reveals how geographic factors such as location, climate, and access to resources affect the distribution of wealth and opportunity. General trends and similarities between different countries and regions regarding the influence of civilizational factors on social and economic polarization are determined. Policy recommendations have been developed to reduce social and economic polarization and promote the sustainable development of countries. Originality. A comprehensive approach was used, combining aspects of culture, history, economics and geography to better understand the essence of social and economic polarization. Cultural factors are considered in greater depth, analyzing in detail the role of language, religion, traditions and identity in the process of forming the social and economic structure. Historical analysis was used and it was determined how historical events influenced modern polarization processes, providing a new level of understanding of this phenomenon. In general, the results of our study make a significant contribution to the understanding of the influence of civilizational factors on the social and economic polarization of countries and open up new opportunities for further research and development of political strategies. Practical value. A detailed analysis of historical events that influenced modern polarization processes was carried out, providing a new level of understanding of this phenomenon. A comprehensive approach is applied, which combines geopolitical, cultural and economic aspects of the life of different countries and regions, to improve the understanding of the essence of social and economic polarization. In general, the results of our research will significantly expand the influence of civilizational factors on the social and economic polarization of countries, which opens up new opportunities for further research and development of strategic vectors for overcoming polarization.